Penerapan Metode Bercerita dalam Meningkatkan Kemampuan Menyimak Anak Usia Dini Usia 5-6 Tahun di TK Pembina Pegasing, Kec. Pegasing, Kab. Aceh Tengah - Irma Qurata Aini; Fauziah Nasution; Ahmad Syukri Sitorus (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to find out: To see the listening ability of young children before using the storytelling method at the Pembina Pegasing Kindergarten, to see the implementation of learning using the storytelling method in the Pembina Pegasing Kindergarten, and to see how the listening ability of early childhood can be improved after using the storytelling method at Pembina Pegasing Kindergarten. The research technique used was PTK (classroom action research) with a quantitative and qualitative approach. The subjects in this study were 9 children aged 5-6 years. The research was carried out in July until completion starting from preparation activities to implementation. Namely in the Orchid class, there are 9 children with 4 boys and 5 girls. This research was conducted at the Pembina Pegasing Kindergarten for the 2023/2024 academic year. The research was conducted in the even semester of FY. 2023-2024 until completion. This research uses the Kemmis and Mc model design. Taggart, this research was carried out in 2 cycles, namely cycle I and cycle II. Cycle I obtained a percentage value of 8.2%. . Cycle II percentage value is 10%. From research conducted starting in Pre-action, Cycle I and Cycle II, it shows that the average child has improved. The increase in children's listening ability shows that using the storytelling method is more effective in improving the listening ability of children aged 5 - 6 years. Thus, the storytelling method is one effort that can improve the listening skills of children aged 5 - 6 years.